IMPACT OF THE SIMBA KUAT PROGRAM (RAMBA SYNERGY IN THE FIELD OF SUPPORTING CLEAN AND HEALTHY LEISURE) ON HANDLING STUNTING - Setiawan, Hanif; Putra, Erwin Hendra; Hendrawan, Wawan; Aprilia, Eka; Rosadi, Hengky; Sari, Dewi Ratna (International Journal of Social Service and Research, 2024)
This paper seeks to analyze the impact of the Strong Synergy Program to Support Clean and Healthy Villages through the concept of "From Waste to Happy Community." Based on data that has been collected from posyandu activities in May 2024 in Keluang Village, Tungkal Ilir District, Banyuasin Regency, there are 8 toddlers experiencing stunting and malnutrition conditions out of 40 toddlers who attended the activity. The program is designed to reduce the amount of wood waste thrown away and reduce the negative impact caused, provide educational play tools that can improve the quality of children's learning and stimulation, help improve stunting conditions through better cognitive and motor stimulation, and provide economic opportunities for local artisans and drive the community's economy. This paper and the program can be a breakthrough in synergistic innovation, where it is a combination of environmental solutions with health and education interventions in Indonesia.